2011
DOI: 10.1051/0004-6361/201016026
|View full text |Cite
|
Sign up to set email alerts
|

An optical spectroscopic survey of the 3CR sample of radio galaxies with z  <  0.3

Abstract: From an optical spectroscopic survey of 3CR radio galaxies with z < 0.3, we discovered a new spectroscopic class of powerful radioloud AGN. The defining characteristics of these galaxies are that compared with radio galaxies of similar radio luminosity they have: a [O III]/Hβ ratio of ∼0.5, indicative of an extremely low level of gas excitation; a large deficit of [O III] emission; and radio core power. We interpret these objects as relic AGN, i.e. sources that experienced a large drop in their level of nuclea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Moreover, further evidence for intermittency of the fuel supply is provided by mid‐IR spectroscopic observations of ULIRGs which, despite generally being considered to represent the final stages of gas‐rich mergers (within ∼100 Myr of coalescence of the nuclei; Rodríguez‐Zaurín et al ), show a considerable range in the level of nuclear AGN activity, with the AGN energetically dominant in <50 per cent of cases (Veilleux et al ). We also note that, based on the detailed analysis of their optical emission‐line spectra, it has been suggested that the AGN in some other WLRG have only recently switched off (Capetti et al ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, further evidence for intermittency of the fuel supply is provided by mid‐IR spectroscopic observations of ULIRGs which, despite generally being considered to represent the final stages of gas‐rich mergers (within ∼100 Myr of coalescence of the nuclei; Rodríguez‐Zaurín et al ), show a considerable range in the level of nuclear AGN activity, with the AGN energetically dominant in <50 per cent of cases (Veilleux et al ). We also note that, based on the detailed analysis of their optical emission‐line spectra, it has been suggested that the AGN in some other WLRG have only recently switched off (Capetti et al ).…”
Section: Discussionmentioning
confidence: 73%
“…However, if the AGN has switched off completely over this period, and the AGN is the only source of ionization for the [O iii ] emission, then we would expect to observe negligible [O iii ] flux in most WLRGs. This is because the e‐folding time of the intensity decline in the [O iii ] emission is only ∼20 yr for a typical NLR electron density of n e = 100 cm −3 (Binette & Robinson ; Capetti et al ). In contrast, we do detect weak but significant [O iii ] emission from all three WLRGs in the high‐power radio galaxy sample described above.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that high-luminosity radio sources have optical spectra that usually exhibit strong emission lines like Hα, [NII]λλ6548, 6584, [OIII]λλ4959, 5007, and Hβ (see e.g. Buttiglione et al 2009aButtiglione et al , 2009bHardcastle, Evans & Croston 2009;Capetti et al 2011).…”
Section: Distribution Of Xuvmentioning
confidence: 99%
“…We classify those remaining two as extremely low excitation radio galaxies (ELERGs) based on their unusually low [OIII]/Hβ of 0.57 and 0.67, respectively, which is consistent with the [OIII]/Hβ ∼ 0.5 indicative of extremely lowexcitation sources. Capetti et al (2011) describe extremely low-excitation galaxies as "radio relics" i.e., sources which recently experienced a drop in nuclear activity -perhaps this is the case in NGC 315 and NGC 541. We see no issues with this interpretation for NGC 541 but NGC 315 shows a warm thermal MIR component.…”
Section: Discussionmentioning
confidence: 99%